Congenital Suborbital Undifferentiated Sarcoma in a Crossbred Calf - Joana G. P. Jacinto; Marilena Bolcato; Arcangelo Gentile; Cinzia Benazzi; Luisa Vera Muscatello (Animals, 2021)
Undifferentiated sarcomas are rare conditions that represent a group of unclassified sarcomas. The purpose of this study is to describe the clinical and pathological features of a calf showing a congenital infiltrating suborbital mass suggestive of undifferentiated sarcoma. The animal was referred because of respiratory distress and the presence of a right suborbital mass since birth. At ultrasonography, the mass displayed an irregular shape with multiple cavities. Radiographs revealed a diffuse, poorly defined mass with different densities overlying the bony structures of the skull. Endoscopy showed a co-involution of the mass in the right side with extension into the nasopharynx. Post-mortem examination showed a round, poorly demarcated neoplasia infiltrating the nasal turbinate and displacing the nasal septum. Histologically, the subcutis was expanded by lobules and bundles of densely cellular neoplastic spindle cells. The neoplasm infiltrated the underlying muscles, bone and the right retromandibular lymph node. The neoplastic cells had a diffuse intense cytoplasmic immunexpression to vimentin, and were negative to cytokeratin AE1/AE3, desmin, MUM1, IBA1, melan A, chromogranin and synaptophysin.